An adiabatic spectroscopic investigation of the CsRb system in ground and numerous excited states. (October 2017) - Souissi, Hanen; Jellali, Soulef; Maha, Chaieb; Habli, Héla; Oujia, Brahim; Gadéa, Florent Xavier
Highlights: Investigation the potential energy curves. Determination the spectroscopic properties. Investigation the electric dipole moments and vibrationel levels of diatomic molecules. Abstract: Via ab-initio approximations, we investigate the electronic and structural features of the CsRb molecule. Adiabatic potential energy curves of 26 1, 3 Σ +, 18 1, 3 Π and 6 1, 3 Δ electronic states with their derived spectroscopic constants as well as vibrational levels spacing have been carried out and well explained. Our approach is founded on an Effective Core Potential (ECP) describing the valence electrons of the system. Using a large Gaussian basis set, the full valence Configuration Interaction can be applied easily on the two-effective valence electrons of the CsRb system. Furthermore, a detailed analysis of the electric dipolar properties has been made through the investigation of both permanent and transition dipole moments (PDM and TDM). It is significant that the ionic character connected with electron transfer that is linked to Cs + Rb − state has been clearly illustrated in the adiabatic permanent dipole moment.